Perancangan Business Intelligence Dashboard Sales Performance - Sunendar, Nendi (Innotech: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
Businesses need accurate and timely information, especially when it comes to salesman training to address concerns about keputusan, especially for manual management systems, risks associated with data input, and difficulties in conducting thorough analysis of sales to create less-than-ideal strategic plans. Because of this, the goal of the research is to develop and refine a data-based dashboard that can provide information in a clear and understandable manner. This dashboard is built using methodologies that include system analysis, data warehouse design, ETL (Extract, Transform, Load), and system design using ASP.NET and Microsoft SQL Server. The ETL process is crucial for ensuring that data integration, extraction, and transformation occur so that operational data is stored in an understandable manner and dashboards that are developed can show the progress of work.